2020
DOI: 10.1021/acs.jpclett.0c02640
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Nanozymes: Engineered Gold Nanoparticles Exhibit Tunable Plasmon-Enhanced Peroxidase-Mimicking Activity

Abstract: Enzyme-mimicking inorganic nanoparticles, also known as nanozymes, have emerged as a rapidly expanding family of artificial enzymes that exhibit superior structural robustness and catalytic durability when serving as the surrogates of natural enzymes for widespread applications. However, the performance optimization of inorganic nanozymes has been pursued in a largely empirical fashion due to lack of generic design principles guiding the rational tuning of the nanozyme activities. Here we choose Au surface-rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…This can create an increase in the local concentration of OH radicals and therefore increase the reaction rate for the formation of oxTMB. 23,45,46 This hypothesis would support the significant enhancement of the NSs and NRs relative to the NPs and support the results in which the NSs are compared with the NRs. In the NSs, there was an increase in activity relative to the Au NPs due to nanoconfinement effects, a higher surface-to-volume ratio relative to the Au NPs enabled by the nanoshell/porous morphology, and the absence of citrate as the stabilizer.…”
Section: Dalton Transactions Papersupporting
confidence: 80%
See 2 more Smart Citations
“…This can create an increase in the local concentration of OH radicals and therefore increase the reaction rate for the formation of oxTMB. 23,45,46 This hypothesis would support the significant enhancement of the NSs and NRs relative to the NPs and support the results in which the NSs are compared with the NRs. In the NSs, there was an increase in activity relative to the Au NPs due to nanoconfinement effects, a higher surface-to-volume ratio relative to the Au NPs enabled by the nanoshell/porous morphology, and the absence of citrate as the stabilizer.…”
Section: Dalton Transactions Papersupporting
confidence: 80%
“…The oxidation of 3,3′,5,5′-tetramethylbenzidine (TMB) was used to evaluate the catalytic performance ( peroxidase-like activity) of the Au NPs, AgAu NSs, or Au@AgAu NRs. 23 The oxidation reactions were carried out in 2 mL centrifuge tubes con-…”
Section: Synthesis Of Au@agau Nanorattles and Agau Nanoshellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 131 ] Optically active plasmonic nanozymes (AuNPs) exhibits enhanced peroxidase‐mimicking activity. [ 132 ] Nanozymes can also be endowed with multifunctional capability. Recently, experimentally derived multifunctional nanozyme based on MOFs, which contains catalytic Cu 2+ and luminescent Tb 3+ ions are also reported.…”
Section: Nanozymesmentioning
confidence: 99%
“…[21][22][23] Few works have described phenomena such as self-catalysis and self-limiting activity of AuNPs, light-triggered plasmonic excitation of catalysis, electrostatic neutralization-controlled catalysis, molecular imprinting-induced selective catalysis, and metal ionassisted catalysis. [24][25][26][27][28][29][30] Our previous study demonstrated the self-catalyzed in situ deposition of AgNPs on surfaces of polydopamine-coated AuNPs. 31 The corona-like AgNPs@AuNP show spectral blue-shift and high activity.…”
Section: Introductionmentioning
confidence: 98%